2019
DOI: 10.3390/toxins11040187
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers for Exposure as a Tool for Efficacy Testing of a Mycotoxin Detoxifier in Broiler Chickens and Pigs

Abstract: Applying post-harvest control measures such as adding mycotoxin detoxifying agents is a frequently-used mitigation strategy for mycotoxins. EFSA states that the efficacy of these detoxifiers needs to be tested using specific biomarkers for exposure. However, the proposed biomarkers for exposure are not further optimized for specific target species. Hence, the goal of this study was a) to evaluate the most suitable biomarkers for deoxynivalenol (DON) and zearalenone (ZEN) in porcine plasma, urine and feces; and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 28 publications
(47 citation statements)
references
References 60 publications
2
45
0
Order By: Relevance
“…The correlation coefficient ( r ) for AFB1 is 0.974, for OTA 0.968 and for DON-sulphate (DON-S) 0.960. DON-S is considered the best biomarker after the exposure of broiler chickens to DON [25]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The correlation coefficient ( r ) for AFB1 is 0.974, for OTA 0.968 and for DON-sulphate (DON-S) 0.960. DON-S is considered the best biomarker after the exposure of broiler chickens to DON [25]…”
Section: Resultsmentioning
confidence: 99%
“…This resulted in the administration of 0.5 mg DON·kg −1 BW as described in [34]. For ZEN, OTA and AFB1 in pigs and AFB1 and OTA in broiler chickens, the administered doses corresponded to the doses previously administered in toxicokinetic studies and studies to determine the efficacy of mycotoxin detoxifiers [25,35]. At these mycotoxin inclusion rates, no clinical symptoms were observed in this study or in previous studies.…”
Section: Methodsmentioning
confidence: 97%
“…A significant decrease of 47% in AUC was observed after the CC administration compared to PO administration indicating that the calcined clay was effective in binding AFG1. Lauwers et al [ 57 ] stated that the detoxifier was effective in binding mycotoxins when the AUC was significantly lower when compared to the AUC without detoxifier in plasma and urine, whereas the k el was not significantly different between the three groups. In addition, no significant difference was observed in maximum concentration and time to maximum concentration.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, no significant difference was observed in maximum concentration and time to maximum concentration. A recent study showed a significant influence of a mycotoxin-detoxifying agent on the AUC of AFB1 in broiler chickens [ 57 ]. In the same study, the authors did not observe any significant difference in C max and T max .…”
Section: Discussionmentioning
confidence: 99%
“…Hence, it is possible that the feed particles compete with the adsorbent and hence, the efficacy of the binder decreases [15]. Furthermore, Lauwers et al demonstrated that the ratio between the concentration of mycotoxins and binder may also influence the binding efficacy [32]. Hence, a too low dose of the product could also have been the reason no effect was seen on the free ZEN concentration.…”
Section: Binders In Feed Normal Rumen Ph (68)mentioning
confidence: 99%